2017
DOI: 10.1016/j.pediatrneurol.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Universal Head Ultrasound Screening in Full-term Neonates: A Retrospective Analysis of 6771 Infants

Abstract: The number of significant anomalies detected by head ultrasound screening in asymptomatic full-term neonates born during the study period was low. Therefore, there is no indication for routine general head ultrasound screening in these patients. However, even if low, in neonates who have neurological abnormalities, risk factors or suspected brain malformations, head ultrasound screening may play an important role in the early diagnosis of intracranial anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
9
2
3
Order By: Relevance
“…Similar to the results of Hsu et al and Ballardini et al, the most common minor findings were subependymal cysts, followed by choroid plexus cysts. 6,7 The incidence rate of subependymal cysts in our study was higher than that of previous study (8.99% vs 5%). 10 The proportion of neonates who had choroid plexus cysts in this study was lower than that in the study of Hung and Liao (2.43% vs 8.8%).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Similar to the results of Hsu et al and Ballardini et al, the most common minor findings were subependymal cysts, followed by choroid plexus cysts. 6,7 The incidence rate of subependymal cysts in our study was higher than that of previous study (8.99% vs 5%). 10 The proportion of neonates who had choroid plexus cysts in this study was lower than that in the study of Hung and Liao (2.43% vs 8.8%).…”
Section: Discussioncontrasting
confidence: 67%
“…6 Ballardini et al showed that in 6771 full-term neonates, the incidence rates of abnormal findings and major abnormalities were 1.7% and 0.19%, respectively. 7 The incidence rates of any ultrasound abnormalities can be as high as 20%. 3 In our study, 17.3% of healthy neonates had abnormal CUS findings, of whom 0.28% presented with major anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 117 neonates without an indication for CU, but with CU conspicuities, 85.5% had MCs and 14.5% had SCs. Ballardini et al postulated a prevalence of 1.7% for conspicuous CUs in asymptomatic neonates aged > 37 weeks GA, and the distribution of MCs and SCs was similar to that in the present study [10]. The prevalence of SCs was 0.33% in group II, which was higher than the prevalence of significant anomalies found by Ballardini et al (0.19%) or that found by Wang et al (0.25%) [10, 11].…”
Section: Discussionsupporting
confidence: 91%
“…While in our prospective cohort study a substantial number of non-specific, non-contributory incidental findings were seen on routine CUSS (n = 34, 17.0 %), no relevant intracerebral or cranial pathology or skull fracture was detected using cerebral ultrasonography imaging. In comparison to the study by Ballardini et al [27] including 6771 healthy term neonates, the rate of incidental findings in our cohort was substantially higher. It is of note that only 114 of 6771 (1.7 %) presented ultrasound abnormalities in their study, while 6657 were normal or exhibited insignificant findings.…”
Section: Discussioncontrasting
confidence: 90%
“…In 101 of 114 (88.6 %) abnormalities were minor, and only 13 infants had major abnormalities (0.19 % of all full-term newborns). Importantly, all neonates with major abnormalities presented with either microcephaly or abnormal neurological evaluations, and only one individual with major abnormalities was detected exclusively by ultrasound [27].…”
Section: Discussionmentioning
confidence: 99%